Co-Creating a Tourism Product: Case St. Lapland - Mattila, Niina (Rovaniemen ammattikorkeakoulu, 2011)
The objective of this thesis was to redevelop a tourism product package, Rivers and Trails, for the export group St. Lapland. The original product was created to increase the customer flows for the summer and the autumn seasons. The purpose for the redevelopment was to improve the product to be more meaningful for the customers. The current situation of the product was studied using qualitative research methods; observation and interviews. The observation was conducted on the Study Tour for Leisure Travel Professionals in Kuusamo after which four representatives of mid-European tour operators were interviewed. Based on the study results development ideas were suggested to improve the product. The Product Developer’s Handbook created as a result of the Tourism Integrated Product Development -project was used as a theory basis for this thesis. The research findings show that small family-owned companies are highly respected in the tourism field. Well organized products and paying attention to the customers personally contribute to their product quality. However, the customers require a degree of privacy and more choices to activities. The redevelopment of the Rivers and Trails -product began with specifying the theme, unifying the product and creating more options. The value of the different product elements were increased with small improvements and procedure changes. The thesis also suggests some product development tools for St. Lapland to better create possibilities to meaningful experiences. Opinnäytetyön tavoitteena oli kehittää St. Lapland-vientirenkaalle työharjoitteluni aikana kokoamaa matkailutuotepakettia Rivers and Trails. Alkuperäinen tuote kehitettiin kasvattamaan asiakasvirtaa kesä- ja syyskaudella. Kehittämisen tavoitteena oli luoda tuotteesta asiakkaalle elämyksiä mahdollistava kokonaisuus. Lähtökohtana opinnäytetyössä oli selvittää Rivers and Trails -tuotteen nykytila asiakkaan näkökulmasta ja löytää kehitysideoita tuotteen parantamiseksi. Opinnäytetyössä käytettiin menetelminä havainnointia ja ...